Stroke as the Sole Manifestation of Takayasu Arteritis in a 15-Year-Old Boy with Latent Tuberculosis - Benjaminsen, Espen (Case Rep Neurol Med, 2016)
Introduction. Takayasu arteritis is a rare disease affecting the aorta and its main branches, causing arterial claudication and end-organ ischemia, including stroke. The etiology is unknown but is believed to be autoimmune. An association between Takayasu arteritis and tuberculosis has been suggested, but the possible relation is unclear. Case Presentation. A 15-year-old Somali boy was diagnosed with latent tuberculosis. He had a lesion in the right lung, and both the tuberculin skin test by the Mantoux method and Quantiferon GOLD test turned out positive. After he suffered a cerebral infarct in the right hemisphere, childhood Takayasu arteritis was diagnosed. The diagnosis was based on diagnostic imaging showing a high-grade stenosis of the origin of the right common carotid artery, an occluded common carotid artery on the left side, a circumferential thickening of the vessel walls in the right and left common carotid artery, and laboratory findings with elevated C-reactive protein. Conclusion. Takayasu arteritis is an uncommon cause of stroke. It should however be kept in mind as a cause of cerebrovascular disease, especially in the young.